Chimeric DCL1-Partnering Proteins Provide Insights into the MicroRNA Pathway - Reis, Rodrigo S.; Eamens, Andrew L.; Roberts, Thomas H.; Waterhouse, Peter M. (Frontiers in Plant Science, 2016)
In Arabidopsis thaliana, efficient microRNA (miRNA) production requires DICER-LIKE1 (DCL1) with the assistance of a partnering protein, DOUBLE-STRANDED RNA BINDING1 (DRB1) or DRB2. The presence of either of these DRB proteins is crucial to determine the mode of action of a miRNA; i.e. cleavage or translation inhibition. Here we studied the structural determinants for the role of DRB1 and DRB2 in the miRNA pathway. We developed a series of chimeric vectors encoding different functional domains of DRB1 and DRB2, and expressed these in the drb1 mutant background in Arabidopsis under the control of the native DRB1 promoter. Complementation of the drb1 developmental phenotype was used to assess the biological role that each functional domain of DRB1 and DRB2 mediates in the miRNA-guided transcript cleavage pathway. The DRB1 amino acid sequence differs considerably to that of DRB2, and analysis of drb1 transgenic lines revealed that the first dsRNA-binding domains (dsRBD1) of DRB1 and DRB2 are functionally similar; in contrast, the dsRBD2 of DRB1 and DRB2 appear functionally distinct. Our bioinformatic analysis further suggests that the C-terminal domain of DRB2 mediates a functional role in the miRNA pathway, whereas its counterpart in DRB1 is known to be dispensable. Our results provide evidence for the differences between DRB1 and DRB2 proteins in vivo, which may be essential for the selection of the miRNA regulatory mechanisms, and suggest that these features are conserved among land plants.